Crystal structure and Hirshfeld surface analysis of 3-[(1E)-(4-{4-[(E)-(3-hydroxybenzylidene)amino]phenoxy}phenylimino)methyl]phenol - Shaaban K. Mohamed; Joel T. Mague; Mehmet Akkurt; Farouq E. Hawaiz; Sahar M. I. Elgarhy; Elham A. Al-Taifi (Acta Crystallographica Section E: Crystallographic Communications, 2021)
In the crystal, the molecule of the title compound, C26H20N2O3, has crystallographically imposed twofold rotation symmetry. The crystal packing consists of layers parallel to the ab plane formed by O—H...N and C—H...O hydrogen bonds. Between the layers, C—H...π interactions are observed.